Strategi Penerapan Kebijakan Keselamatan dalam Sistem Pelayaran (Studi Pada PT. Pelayaran Nusantara Sejati) - Erhanuddin Erhanuddin (Journal of Innovative and Creativity, 2025)
This study aims to analyze the implementation of maritime safety policies at PT. Pelayaran Nusantara Sejati, focusing on the challenges and strategies implemented in the safety management system. Although the company has adopted national regulations related to maritime safety, such as Law Number 17 of 2008 and Minister of Transportation Regulation Number PM 57 of 2021, the implementation of these policies still faces obstacles, such as inadequate quality of crew training, limited safety facilities, and irregular supervision. This study identified that the main factors hindering the effectiveness of safety policies are the gap between regulations and field practices, as well as a weak safety culture among ship crews. To address these obstacles, PT. Pelayaran Nusantara Sejati has implemented a Hazard and Operability Study (HAZOP)-based risk management approach, as well as strengthening its crew training program, internal safety audits, and the application of digital technology to detect potential hazards more quickly. The results of the study indicate that improvements in practical training, better communication between management and ship crews, and more consistent monitoring and evaluation are essential to improve maritime safety. This study is expected to provide useful recommendations for PT. Pelayaran Nusantara Sejati in improving its safety management system and creating a safer working environment for crew.